Реплантация - за и против. Клинический случай реплантации корня, разрушенного и восстановленного культевой вкладкой, с целью сохранения мостовидной конструкции, включающей проблемный зуб, в области которого возник свищевой ход (Эндодонтия Today)
This paper presents a complex clinical case of replantation of root, in order to preserve as orthopedic rehabilitation of bridge structures, including the problematic tooth, in which there was fistulous course. During the re-endodontic treatment destroyed the root of the tooth has been extracted from the wells of the alveolar ridge and processed, curettage of the wells is made, after which the root of the newly implanted inside. After 3 weeks root inlay was set, temporary bridge is produced, including the tooth.